Breaking into acting for dummies - Garrison, Larry; Wang, Wallace (New Jersey John Wiley and Sons, Inc., 2021)
"Breaking Into Acting For Dummies demystifies the behind-the-curtain side of showbiz to help you understand how it really works, who the decision-makers are, what they're looking for when they're picking talent, and how to get them on your side. Written by two friendly insiders, this guide will help you map out your plan of attack, showing you how to open doors--and keep them open--and use your time wisely. You'll understand how to flesh out your professional persona, craft your resume, and judge the angle of your headshots and webcam appearances. Once you've mastered these skills, it's time to go to market as your own publicity department, building your media and online presence until everyone who's anyone knows exactly who you are"-- Publisher's description.
Part 1 : Figuring out the business of acting. Staying on top of the changes in show business -- Discovering how show business has changed and adapted -- From agents, managers, and unions : introducing the movers and shakers -- Part 2 : Packaging and marketing yourself. Making a great first impression with a head shot and samples of your work -- Creating a five-star acting resume -- Training to improve your acting skills -- Part 3 : Taking your first steps into show business. Representing yourself, networking, and promoting yourself on websites -- Seeking representation : an agent, manager, and/or an entertainment attorney -- Auditioning : the art of what you need to know -- Understanding diversity challenges in show business -- Adapting to difficult personalities.

Part 4 : Scoping out the markets. Acting in film and television -- Acting in commercials -- Acting in theater -- Performing without being seen : voice-over acting -- Working as an extra -- Getting your kid into show biz.

Part 5 : Managing your money as an actor. Don't get ripped off! Avoiding con games, scams, and self-destruction -- Working to pay your bills until you hit it big -- Managing your finances.

Part 6 : The Part of tens. Ten myths debunked about show business -- Ten traits of successful actors -- Ten tips for improving as an actor -- Ten ways to act just for the fun of it.
Includes index (pages 319-333).
Keywords: Acting -- Economic aspects; Acting -- Vocational guidance